Thermal Solid–Solid Transformation Synthesis of Zinc Anchored in Hierarchical Porous N-Doped Carbon for Efficient CO2 Applications; Energy and Fuels; Vol. 37, iss. 3 - Somboon Chaemchuen; Xiaotong Hou; Zhonghan Cheng; Kui Zhou; Serge Zhuiykov; Verpoort F. V. K. Frensis Valter Kornelius (2023, 2023)
Title screen